Case Report: Successful treatment of steroid-refractory graft-vs.-host disease following bilateral lung transplantation - McCormick, Benjamin J.; Rusanov, Victoria; Tao, Zhuo; Kaleekal, Thomas; Wille, Keith; Espinoza-Gutarra, Manuel R. (Frontiers in Transplantation, 2025)
Graft-vs.-host disease (GVHD) is a rare but potentially fatal complication following solid organ transplantation (SOT), with limited reported cases and high mortality rates after lung transplantation. We present a case of steroid-refractory GVHD (SR-GVHD) following bilateral lung transplantation and review the literature on GVHD in SOT. A patient developed SR-GVHD affecting the skin, gut, liver, and bone marrow following bilateral lung transplantation. Initial treatment with high-dose corticosteroids was ineffective. Subsequent therapy with rabbit anti-thymocyte globulin (rATG) and ruxolitinib led to complete remission over two months. Short tandem repeat (STR) analysis aided in diagnosis and monitoring. This case highlights the importance of early diagnosis and aggressive treatment of GVHD following SOT. We propose a treatment algorithm including rapid escalation to multi-agent immunosuppression for SR-GVHD. Interdisciplinary collaboration between solid organ and stem cell transplant specialists is crucial. Further research is needed to identify optimal strategies for prevention and treatment of GVHD in SOT recipients.